1986
DOI: 10.1159/000146221
|View full text |Cite
|
Sign up to set email alerts
|

Surface Area of the Atlanto-Occipital Articulations

Abstract: The surface areas of the occipital condyles of 101 skulls and of the superior articular facets of 103 atlases have been measured to ascertain bilateral asymmetry and dominance. The atlases show a tendency to have larger facets and the occipital bones tend to have larger condyles on the right side.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 1 publication
2
11
0
Order By: Relevance
“…For this reason, ATDs have their upper neck load cell located at the OCs. The condyles, which have both length and area (Mysorekar and Nandedkar, 1986;Febbo et al, 1992;Bozbuga et al, 1999), have not been quantitatively located with respect to cranial landmarks (Byars et al, 1970;Hubbard and McLeod, 1973;Butler, 1992). Interestingly enough, few studies even suggest a geometric location of the OCs McLeod, 1973, 1974;Butler, 1992).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, ATDs have their upper neck load cell located at the OCs. The condyles, which have both length and area (Mysorekar and Nandedkar, 1986;Febbo et al, 1992;Bozbuga et al, 1999), have not been quantitatively located with respect to cranial landmarks (Byars et al, 1970;Hubbard and McLeod, 1973;Butler, 1992). Interestingly enough, few studies even suggest a geometric location of the OCs McLeod, 1973, 1974;Butler, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly enough, few studies even suggest a geometric location of the OCs McLeod, 1973, 1974;Butler, 1992). Most studies with OC measurements only include a morphometric analysis of the skull base without any reference to cranial anthropometric landmarks (Mysorekar and Nandedkar, 1986;Febbo et al, 1992;Bozbuga et al, 1999;Cicekcibasi et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Method 2, described by Mysorekar and Nandedkar (1986), 10 was also used to determine surface areas. This method consisted of producing moulds of the articular surfaces of the atlas and its respective condyle by pressing a thin strip of aluminum foil, which precisely fitted each bony projection and depression, onto the articular surface of the atlas and the condyle.…”
Section: Methodsmentioning
confidence: 99%
“…Although that study demonstrated anomalies in the surface areas, no data were presented with regard to the preciseness of fit between the articulating surfaces. 10 Based on the information provided above, the objective of this study was to assess matched A/O ipsilateral and contralateral joint articular surfaces in human cadavers in regard to symmetry between opposing joint surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Probably the circular areas represent pressure areas during the movement and rough areas represent the non-articular areas. In general, human beings during their day to day activities tend to incline their heads to one side more than the other and that may influence the amount of articular surface area on each side of the atlas as well as on the occipital condyles (10). Few workers discussed the complete division of superior articular facets and variation in the depth of intact facets from being flat, 3mm or less to 5mm or greater (11).…”
Section: Introductionmentioning
confidence: 99%